N11 Development of a young person clinic for 16-24-year-olds with Inflammatory Bowel Disease (IBD), using a multidisciplinary team (MDT) approach. (21st January 2022) - Hamzawi, M; Hickey, Y; Brannick, S; Brett Kilmurray, O; Jones, F; Sheridan, J; Cullen, G
Abstract: Background: In Ireland, the transition process is ad hoc with no formal guidelines on how to conduct transition clinics. This nurse-led project, aimed to develop a specific young person clinic for adolescents and provide information to adolescents and their families on the service they were joining, before their first clinic visit, subsequently reducing anxiety and improving outcomes. Providing the right care for young people with IBD, in the right place, at the right time, where the patient is a priority, is the end goal. Methods: The successful implementation of this project is due to the collaborative work of a multidisciplinary team using the Health Service Executive (HSE), Peoples Needs Defining Change Guide (2018). This change model provides clear definitive steps to Define, Design and Deliver innovative projects. The model was applied as follows: Define: Raise awareness of the need for adolescent clinic Activate a core change team Develop a vision in line with the organisational culture Design: Propose a care pathway for adolescents including transition. Design an informative 'Welcome Booklet' Arrange Virtual Meet and Greet (due to Covid restrictions) Deliver: Open communication with all relevant stakeholders Determine a time suitable for recurring adolescent clinic Seek input from patients, colleagues and communication team to develop an informative 'Welcome Booklet' Results: The CIPP evaluation model, Context, Input, Process and Product, complimented this change model as formative evaluation throughout. This ensured the change process was streamlined with the values and vision of all stakeholders involved. Context –SWOT analyses was undertaken, and Goals defined Input – Strategy was defined and stakeholder analyses Process –Monthly MDT meetings, design model of care, welcome booklet. Plan virtual introductory meetings due to Covid unable to meet face to face in the paediatric hospital Product – Dedicated recurring clinic time for 16–24-year-olds with IBD to include transition clinics. 100% of parents and 80% of adolescents found the welcome booklet informative and useful. 100% both adolescents and parents found the introductory WebEx meeting beneficial. Commenced RCT to look at best format for transition clinics going forward Conclusion: (HSE), Peoples Needs Defining Change Guide (2018) provided the essential toolkit to ensure leadership, teamwork, the importance of stakeholders while keeping the patient central to all decisions made in developing young person's clinics for 16-24-year-olds with IBD.